2004
DOI: 10.1038/sj.onc.1207324
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of p53 sequence-specific binding by DNA supercoiling

Abstract: Using a new competition assay, we investigated the effect of DNA negative supercoiling on the DNA sequencespecific binding (SSDB) of human wild-type (wt) p53 protein. We found that supercoiled (sc) pBluescript DNAs with different inserted p53 target sequences were stronger competitors than a mixture of scDNA pBluescript with the given 20-mer target oligodeoxynucleotide. ScDNAs were always better competitors than their linearized or relaxed forms. Two DNAs with extruded cruciforms within the target sequence wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…Furthermore, because negatively supercoiled DNA is underwound, it exerts a force that helps separate the two strands of the helix, which is required during both replication and transcription (Clark, 2005). As previously described, a number of protein-DNA complexes only occur because the binding is promoted by negative supercoiling due to stabilization of writhing (Palecek et al, 2004). Recent studies suggest a possible relation between the p53 function and the DNA topology.…”
Section: Amino Acid-nucleic Acids Interaction In Affinity Chromatographymentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, because negatively supercoiled DNA is underwound, it exerts a force that helps separate the two strands of the helix, which is required during both replication and transcription (Clark, 2005). As previously described, a number of protein-DNA complexes only occur because the binding is promoted by negative supercoiling due to stabilization of writhing (Palecek et al, 2004). Recent studies suggest a possible relation between the p53 function and the DNA topology.…”
Section: Amino Acid-nucleic Acids Interaction In Affinity Chromatographymentioning
confidence: 75%
“…Recent studies suggest a possible relation between the p53 function and the DNA topology. Palecek et al (2004) hypothesized that the DNA supercoiling degree may play a significant role in the complex p53-regulatory network.…”
Section: Amino Acid-nucleic Acids Interaction In Affinity Chromatographymentioning
confidence: 99%
“…In addition to small molecules, other factors, like the supercoiled nature of the DNA or local DNA bending, may facilitate p53-DNA interactions. 59,61 Importantly, it has been demonstrated earlier that there is a direct correlation between the stability of p53-DNA complexes and the ability of the DNA to be bent by the p53 DBD upon binding. 68 A summary of the above regulatory effectors is shown in Figure 1.…”
Section: The P53 C-terminal Dna-binding Domainmentioning
confidence: 99%
“…57,58 Though controversial, the importance of the CTD in p53 functioning has been continuing to reveal itself in a number of more recent publications. McKinney and Prives, 59 Fojta et al, 60 and Palecek et al 61 have shown that the CTD is important for binding to various non-linear DNAs. In another study, McKinney et al 62 have demonstrated the involvement of CTD in the ability of p53 to diffuse linearly on DNA.…”
Section: The P53 C-terminal Dna-binding Domainmentioning
confidence: 99%
“…In addition, NMR analysis has shown that wild-type and ⌬Cp53 are identical in conformation and that the CT does not interact with other p53 domains (Ayed et al 2001). In addition to this controversy, recent reports have supported the importance of the p53 CT for p53 binding to nonlinear DNA (McKinney and Prives 2002;Fojta et al 2004;McKinney et al 2004;Palecek et al 2004). Finally, CT modification is necessary for efficient promoter activation mediated by p53 (Liu et al 2004;McKinney et al 2004).…”
Section: Effects Of Ct Modification On P53-inducible Genesmentioning
confidence: 99%